HUBUNGAN BEBAN KERJA DAN MOTIVASI PERAWAT DENGAN KUALITAS DOKUMENTASI ASUHAN KEPERAWATAN - Osi Draini; Endah Ony Afiefi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Nursing documentation is an important tool that can be used as an indicator of nursing care. Quality documentation functions as a means of communication among healthcare workers and as an evaluation tool for healthcare services, as well as an indicator of hospital quality. Incomplete and inaccurate documentation will impact patient safety and reduce the quality of service. The quality of documentation is influenced by various factors, including workload and nurse motivation. The purpose of this study is to determine the relationship between nurse workload and motivation with the quality of nursing care documentation. The research design used a quantitative study with a descriptive analytic method and a cross-sectional approach. The research location was conducted at X Hospital with sampling using the